Interleukin 11 is upregulated in uterine lavage and endometrial cancer cells in women with endometrial carcinoma - Nicholls Peter K; Jobling Tom; Salamonsen Lois A; Yap Joanne; Dimitriadis Evdokia (BMC, 2010)
Abstract Background Interleukin (IL) 11 is produced by human endometrium and endometrial cancer tissue. It has roles in endometrial epithelial cell adhesion and trophoblast cell invasion, two important processes in cancer progression. This study aimed to determine the levels of IL11 in uterine lavage fluid in women with endometrial cancer and postmenopausal women. It further aimed to determine the levels of IL11 protein and its signaling molecules in human endometrial cancer of varying grades, and endometrium from postmenopausal women and IL11 signalling mechanisms in endometrial cancer cell lines. Methods IL11 levels in uterine lavage were measured by ELISA. IL11, IL11 receptor(R) α, phosphorylated (p) STAT3 and SOCS3 were examined by immunohistochemistry in endometrial carcinomas and in control endometrium from postmenopausal women and normal cycling women. The effect of IL11 on pSTAT3/STAT3 and SOCS3 protein abundance in endometrial cancer cell lines and non-cancer endometrial epithelial cells was determined by Western blot. Results IL11 was present in uterine flushings and was significantly higher in women with Grade 1 carcinomas compared to postmenopausal women (p < 0.05). IL11 immunostaining was significantly elevated in the endometrial tumour epithelial cells from Grade 1 and 3 compared to endometrial epithelium from postmenopausal and cycling women. IL11Rα immunostaining intensity was increased in cancer epithelium in the Grades 1 and 2 tumours compared to epithelium from postmenopausal women. Both IL11 and IL11Rα localized to vascular endothelial and smooth muscle cells while IL11 also localized to subsets of leucocytes in the cancer tissues. pSTAT3 was found in both the tumour epithelial and stromal compartments but was maximal in the tumour epithelial cells, while SOCS3 was predominantly found in the tumour epithelial cells. pSTAT3 staining intensity was significantly higher in Grade 1 and 2 tumour epithelial cells compared to epithelial cells from cycling and postmenopausal women. SOCS3 staining intensity did not differ between between each tumour and postmenopausal endometrial epithelium but SOCS3 in cycling endometrium was significantly higher compared to postmonopausal and Tumour Grades 2 and 3. IL11 increased pSTAT3/STAT3 in all tumour cell lines, while SOCS3 abundance was increased only in one tumour cell line. Conclusions The present study suggests that IL11 in uterine washings may be useful as a diagnostic marker for early stage endometrial cancer. It indicates that IL11, along with its specific receptor, IL11Rα, and downstream signalling molecules, STAT3 and SOCS3, are likely to play a role in the progression of endometrial carcinoma. The precise role of IL11 in endometrial cancer remains to be elucidated.